A comparative study of cone-beam computed tomography and digital panoramic radiography for detecting pulp stones - Tassoker, Melek (Imaging Sci Dent, 2018)
PURPOSE: The aim of this study was to compare cone-beam computed tomography (CBCT) and digital panoramic radiography (DPR) for the detection of pulp stones. MATERIALS AND METHODS: DPR and CBCT images of 202 patients were randomly selected from the database of our department. All teeth were evaluated in sagittal, axial, and coronal sections in CBCT images. The systemic condition of patients, the presence of pulp stones, the location of the tooth, the group of teeth, and the presence and depth of caries and restorations were recorded. The presence of pulp stones in molar teeth was compared between DPR and CBCT images. RESULTS: Pulp stones were identified in 105 (52.0%) of the 202 subjects and in 434 (7.7%) of the 5,656 teeth examined. The prevalence of pulp stones was similar between the sexes and across various tooth locations and groups of teeth (P>.05). A positive correlation was observed between age and the number of pulp stones (ρ=0.277, P<.01). Pulp stones were found significantly more often in restored or carious teeth (P<.001). CBCT and DPR showed a significant difference in the detection of pulp stones (P<.001), which were seen more often on DPR than on CBCT. CONCLUSION: DPR, as a 2D imaging system, has inherent limitations leading to the misinterpretation of pulp stones. Restored and carious teeth should be carefully examined for the presence of pulp stones. CBCT imaging is recommended for a definitive assessment in cases where there is a suspicion of a pulp stone on DPR.